Gait Analysis and Trajectory Planning of a Hybrid Dual-platform Staggered Hexapod Robot - Wang Chunzhen; Li Ruiqin; Chai Chao; Wang Zhihao; Fan Wenlong (Jixie chuandong)
A novel hybrid dual-platform staggered hexapod robot based on R&(2-UPU/2-RPR) hybrid mechanism is proposed, and the structure of the robot is designed. The hexapod robot relies on the mutual dislocation of the upper and lower platforms of a 2-UPU/2-RPR parallel mechanism to generate the walking action. The parallel mechanism is also used as a body connecting two groups of three legs, so that the robot can achieve “3+3” gait walking with less driving. The body of the hexapod robot is connected in series with the loading platform by a relative rotation structure, which can realize 360° flexible turning with zero radius. The inverse position solution of the parallel mechanism is obtained based on the RPY transformation matrix. The maximum step length, the maximum zero radius turning angle of a single turn in an intermittent period of the hexapod robot and the trajectory curve of the hexapod robot are obtained by analyzing the mutual interference constraints of the legs and driving constraints of the hexapod robot. The gait of the hexapod robot walking on flat ground and climbing steps is analyzed. Finite element analysis results on its load capacity show that the hexapod robot can replace the porter and has a wide range of potential applications.